Demarcating the Use and Misuse of Epistemic and Deontic Modality Operators in Some Translated Verses of Surah Al-Kahf: A Systemic Functional Approach - Abdulaa, Mohammad (Jordan Journal of Modern Languages & Literatures, 2022)
The meager Arabic literature on modality was one of the pivotal impediments that challenged non-Arab translators when interpreting Qur’an verses. That being so, this study attempts to highlight some epistemic and deontic modality bloopers in some translated verses in Surah Al-Kahf (18:1-21). This modality investigation was carried out within the theoretical framework of the values and realizations of English and Arabic modality systems set by Halliday and Matthiessen (2004) and Anghelescu (1999). The results showed that, first, translators should not use English epistemic possibility modals with low values when rendering Arabic verbs in the subjunctive mood. Second, some Arabic conjunctions such as “وأ” ‘or’ convey a degree of possibility that requires an English epistemic possibility adjunct modal to be there in the target text. Third, Arabic verbs with emphatic affixes are better translated with an English modal expressing high degree of inclination. Keywords: Epistemic Possibility, Deontic Modals, Modality, Proposition, Subjunctive and Jussive Moods.